Morphological Diversity of Lansium domesticum Corr in South Sumatra - Rupiah Rupiah Rupiah; Laila Hanum; Zaidan P Negara; Zulkifli Dahlan; Indra Yustian (Science and Technology Indonesia, 2018)
Research on the Morphological Diversity of Lansium domesticum Corr in South Sumatra aims to examine the morphological diversity of L. domesticum in South Sumatra. The research was conducted in April 2017 to June 2017. This research was conducted by means of exploration carried out in seven districts covering, East Ogan Komering Ulu District, South Ogan Komering Ulu District, Ogan Komering Ulu District, Musirawas District, Ogan Komering Ilir District, Muara Enim District and Musi Banyuasin District. Sampling was done using purposive sampling method. Observation of morphological diversity was done by characterization of morphology and analyzed by the descriptive method. The result of this research shows that in South Sumatera, there were two variants of L. domesticum namely L. domesticum variant duku and L. domesticum variant langsat. Morphological characters that distinguish between duku and langsat variants were found under canopy conditions, the presence of hair on top and bottom surfaces of leaves, fruit shape, fruit skin thickness, fruit taste, and the presence of sap on ripe fruit.